E-BOOK MEDIA TRENDS IN THE LEARNING PROCESS AT SCHOOL - Indrawan, I Putu Eka; Kristiyanti, Ni Nyoman Ely; Agustini, Ketut; Sudatha, I Gde Wawan (Indonesian Journal of Educational Development (IJED), 2023)
E-books are digital teaching materials that can be integrated with various multimedia, including images, videos, animations or manipulative media. For the next e-book development process, data and information on what kind of e-book and what media have been integrated are needed. For this reason, a Systemic Literature Review (SLR) was conducted which examined what and how e-books were researched. This research uses PRISMA (Preferred Reporting Items for Systemic and Meta-Analysis) guidelines, by searching for scopus indexed articles in the 2019-2023 range involving a total of 193 articles. After the screening process, 14 articles were obtained which were then analyzed in accordance with the Research Question (RQ) that had been formulated. From the results of the study based on two RQs, it was found that (1) the most research design that examines e-books is design/development research; (2) the least integrated aspect in e-books is animation/manipulative media. These results have limitations in terms of the scope of data sources and the depth of study on the material discussed. So this research provides opportunities for further researchers both in development design and SLR.